Comparative Performance of Textured Yarn Drawn through Apron and Godet in Draw Texturing Machine - Subhankar Maity; Bibekananda Basu; Abhishek Mishra (Tekstilec)
Over the past 20 years, in filament draw texturing, very few developments and innovations have been introduced into production machineries. The growing demand for energy efficiency, faster production rates and greater production flexibility have prompted our investigation into non-traditional approaches to improve yarn control during the texturing. Instead of aprons, small individually driven godets are a solution for high-speed manufacturing, yarn control and energy saving. The drawing godets, where the yarn can be considered an elastic coupling element between two consecutive godets, pose a new challenge for consistency in velocity control. Though some machinery manufacturers have introduced the godet system, the yarn quality produced by the godet system is not systematically evaluated and compared vis-à-vis the apron system. The current study prepared textured yarns in both apron and godet systems while maintaining the same texturing parameters. Differences in the yarn’s bulk, modulus, breaking elongation, tenacity and boiling water shrinkage were assessed and compared. Woven and knitted fabrics were prepared from textured yarns, and a comparative analysis of fabric properties was performed with respect to their tearing strength, air permeability, drape and dyeability. Better quality of yarn and fabrics can be prepared in the godet system, which is energy saving, of higher speed and requires low maintenance technology in comparison to the apron system.